Right Lung Agenesis Associated with Dextrocardia in Adulthood - Krisnanda, Made Yogi; Sriandari, Luh Putu Feby; Darmayanti, Sheila Gerhana; Suwardana, Gede Ngurah Rsi (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Pulmonary agenesis is a rare lung disease, occurring in approximately 1 out of every 100,000 births. Most cases of pulmonary agenesis result in death during the neonatal period. Although survival in cases of pulmonary agenesis is rare, it is possible to encounter lung agenesis in adults. Case: A 26-year-old female patient presented with progressive dyspnea. On physical examination, retraction of the breathing muscles, reduced chest excursions, and decreased breath sounds on the right side were observed. A chest X-ray raised suspicion of pulmonary agenesis. A computed tomography (CT) scan showed hypoplasia of the right lung, accompanied by mediastinal shift, hyperinflation of the left lung, and retraction of the diaphragm and liver to the right. Spirometry showed moderate obstruction. Conclusion: Pulmonary agenesis in adult patients is extremely rare. Chest X-rays and CT scans are the main diagnostic modalities for pulmonary agenesis. There is no specific treatment for asymptomatic cases. Management focuses on conservative and symptomatic care.